Comparison of Immune Effects Between Brucella Recombinant Omp10-Omp28-L7/L12 Proteins Expressed in Eukaryotic and Prokaryotic Systems - Zhu, Lin; Wang, Qiuju; Wang, Yujian; Xu, Yulin; Peng, Duo; Huang, He; Hu, Liping; Wei, Kai; Zhu, Ruiliang (Frontiers in Veterinary Science, 2020)
Brucella, a genus of bacteria that causes brucellosis, infects and threatens domestic animals and humans in endemic areas. Presently, some live attenuated vaccines of Brucella are used to immunize livestock; however, these vaccines are pathogenic to humans, can provoke abortion when administered to pregnant livestock, and induce antibodies in vaccinated livestock that affect the diagnosis of field infection. It is, therefore, very important for improving the safety and immune protection effects of Brucella vaccine. Currently, recombinant protein-based subunit vaccines are considered promising safe and effective alternatives against brucellosis. Here, we separately expressed the recombinant Omp10-Omp28-L7/L12 proteins of Brucella using eukaryotic and prokaryotic expression systems, which were then used as immunogens for evaluating their immune responses. Taishan Pinus massoniana pollen polysaccharides (TPPPS), an already verified natural adjuvant, was utilized to evaluate the immune conditioning effect on the recombinant proteins. Antibody levels, spleen lymphocyte proliferation, percentages of CD4+ and CD8+ T cells, and cytokine secretion in mice were examined after three successive immunizations. The protective effects against Brucella challenge were also evaluated in mice, and used a live vaccine as a positive control. The results indicated that the immune responses of the recombinant Omp10-Omp28-L7/L12 protein groups were significantly higher than those of the PBS control group. The recombinant Omp10-Omp28-L7/L12 protein expressed in Pichia pastoris (P. pastoris) exhibited a slightly higher expression level and immunogenicity than that expressed in Escherichia coli (E. coli), and the Omp10-Omp28-L7/L12 (P. pastoris) + TPPPS group provided the most pronounced immune effect. The protective results showed that the recombinant Omp10-Omp28-L7/L12 proteins expressed in the two expression systems had significantly better protective effects against Brucella melitensis challenge compared with the negative control, and the addition of TPPPS adjuvant could significantly improve the protective effects of subunit vaccines. However, we also noticed that all of the evaluated subunit vaccines induced less protection than the B. melitensis M5 live vaccine. These results indicate that the combination of recombinant Omp10-Omp28-L7/L12 antigen and TPPPS adjuvant shows potential as an effective brucellosis subunit vaccine, and P. pastoris is a preferred expression system to prepare this recombinant subunit antigen.